2014
DOI: 10.1002/j.0022-0337.2014.78.4.tb05706.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Acceptability of High‐Stakes e‐Assessment in Dental Education: Using Privacy Screen Filters to Control Cheating

Abstract: Acceptability is a required quality for a sound assessment. For students, acceptability of a test is strongly inluenced by perception of fairness. Computer-based assessment has been reported to be preferred by students provided that strict controls to prevent cheating are in place. This may be dificult to achieve as e-assessments are often taken in learning environments where computer screens are close together. In this study, 138 Year 5 dental students completed an e-assessment followed by an onscreen post-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Approximately 55% of the students reported no exam dishonesty, while the other half sought assistance from friends or other sources 28 . The acceptance of e‐invigilation was high among the EUC students (mean 4.13, Question 9), a finding that is consistent with previous studies (90% acceptance rate in the study of Escudier et al) 30 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Approximately 55% of the students reported no exam dishonesty, while the other half sought assistance from friends or other sources 28 . The acceptance of e‐invigilation was high among the EUC students (mean 4.13, Question 9), a finding that is consistent with previous studies (90% acceptance rate in the study of Escudier et al) 30 …”
Section: Discussionsupporting
confidence: 89%
“…Another issue deserving particular attention is the e‐invigilation systems used in online exams to prevent cheating and preserve academic honesty. A variety of systems and combination of methods has been used to ensure academic integrity during the online exams: privacy screen filters for on‐site exams, 30 ExamID and ExamMonitor to confirm student identities and to video‐audio monitor them, 43 signed Ethics Pledge in combination with Zoom videoconferencing application (Zoom Communications Inc., San Jose, CA, USA) and with ‘cheating behaviour lists’, 32 face‐tracking movement and artificial intelligence, 31,32 random question sequencing and shuffling in the order of choices 28,32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experiment in Dental Education suggested that a physical barrier would deter cheating. Research by [13] using survey data showed that covering monitors with screen filters increases their acceptability 90% among students, and helps students feel safer while writing exams. It was not clear whether they used randomization methodology, however, it is obvious that using screen filters darkens viewable content by reducing the readability of colorful pathology images.…”
Section: Resultsmentioning
confidence: 99%